Showing our colors : Afro-German women speak out - Ayim, May, 1960-1996; Oguntoye, Katharina; Schultz, Dagmar (University of Massachusetts Press, 1992)
Showing Our Colors: Afro-German Women Speak Out is an English translation of the German book Farbe bekennen edited by author May Ayim, Katharina Oguntoye, and Dagmar Schultz. It is the first published book by Afro-Germans. It is the first written use of the term Afro-German. --